Rheological and thermal behaviour of high impact polystyrene nanocomposite - Al-Ghamdi, Ahmed S.; Ali, Mohammad Yeakub (Trans Tech Publications, Switzerland, 2012)
This paper presents the study of rheological and thermal behaviour of high impact polystyrene/multiwall carbon nanotubes (HIPS/MWCNTs) nanocomposite. The nanocomposite was prepared via melt mixing method. The influence of different loadings of MWCNTs on the HIPS viscosity and other rheological characteristics were analyzed experimentally. Other rheological characteristics were studied using dynamic analysis of viscosity through rotational rehometer. Glass transition temperature (Tg) were also investigated using non-isothermal differential scanning calorimeter analysis. The viscosity was found to be directly proportional to MWCNTs’ loading, up to five times the value of pure HIPS at loading level of 7.5wt% of MWCNTs. The MWCNTs loading demonstrated a marginal effect (1-2%) on the Tg.